Effect of commercially-prepared wax coating on the quality of bell pepper (Capsicum annuum, L.) - Sustiguer, Mayla Delos Santos
The capability of the commercially-prepared wax coating Sta Fresh 320 to extend the storage life of mature green bell peppers was studied.